Dampak Kompensasi, Motivasi dan Kedisiplinan Terhadap Prestasi Kerja Karyawan pada PT. Sumber Alfaria Trijaya - Muhtazib Muhtazib; Mattarima Mattarima (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
The aim of the research is to determine the impact of compensation, motivation and discipline variables on employee work performance at PT. Sumber Alfaria Trijaya, Tbk in Makassar, South Sulawesi Province. And to find out what variables have the most impact on employee work performance at PT. Sumber Alfaria Trijaya, Tbk in Makassar, South Sulawesi Province. The research methods used are quantitative and qualitative research methods. The research results obtained simultaneously show that discipline, motivation and compensation factors have a significant effect on employee work performance at PT. Sumber Alfaria Trijaya, Tbk in Makassar. Partially, discipline, motivation and compensation factors significantly influence employee work performance at PT. Sumber Alfaria Trijaya, Tbk in Makassar. Partially, compensation factors have a dominant influence on employee work performance at PT. Sumber Alfaria Trijaya, Tbk in Makassar.